Postemergence Weed Control with Diflexx, Diflexx Duo, Capreno, and Atrazine in Corn Resistant to Glufosinate and Glyphosate - R. Currie; P. Geier (Kansas Agricultural Experiment Station Research Reports, 2017)
A study was initiated near Garden City, KS, in 2016, comparing the weed control of several postemergence herbicide treatments in irrigated corn. Control of kochia, Palmer amaranth, and crabgrass was 96% or more effective with all herbicides at 7 days after treatment (DAT). By 62 DAT, control of these three weed species was generally best when glyphosate, atrazine, Diflexx (dicamba) or Clarity (dicamba) were included in the herbicide mixture. Although all herbicide tank mixes increased yield compared to the untreated plots, no tank mix resulted in a superior yield.
Keywords: herbicide-resistant corn